2019
DOI: 10.7554/elife.41299
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular domain dynamics regulate synaptic MAGUK protein interactions

Abstract: PSD-95 MAGUK family scaffold proteins are multi-domain organisers of synaptic transmission that contain three PDZ domains followed by an SH3-GK domain tandem. This domain architecture allows coordinated assembly of protein complexes composed of neurotransmitter receptors, synaptic adhesion molecules and downstream signalling effectors. Here we show that binding of monomeric CRIPT-derived PDZ3 ligands to the third PDZ domain of PSD-95 induces functional changes in the intramolecular SH3-GK domain assembly that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 58 publications
6
19
0
Order By: Relevance
“…Surprisingly, we observe that not only α 3 affects the allosteric network in PDZ3, but there is a substantial difference when the domain is studied in isolation as compared to when it is part of the PSG supramodule. This finding is in line with previous studies indicating that the allostery is mediated through interdomain communication by protein-protein interactions (15,18).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Surprisingly, we observe that not only α 3 affects the allosteric network in PDZ3, but there is a substantial difference when the domain is studied in isolation as compared to when it is part of the PSG supramodule. This finding is in line with previous studies indicating that the allostery is mediated through interdomain communication by protein-protein interactions (15,18).…”
Section: Discussionsupporting
confidence: 93%
“…6 A and B). In accordance with previous findings (18,38) we propose that the allosteric network propagates to new sites in the context of the supramodule. Zhang et al, showed that the PSG from PSD-95 changes from compact to extended conformation upon CRIPT binding, which disturbs PDZ3:SH3 Interdomain interactions at the β 1 β 2 loop, β 2 sheet, and α 2 and α 3 helix in PDZ3 (38).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the rate constants differ so that one conformer binds CRIPT faster than the other one, reflecting changes around the binding groove associated with the conformational transition. Previous work demonstrated conformational transitions within the PSG using structural approaches (8,9), and more recently, functional oligomerization has been shown to be dependent on the PSG supramodule (17,(21)(22)(23). The binding kinetics observed in this study could be related to these phenomena.…”
supporting
confidence: 55%